Technology Assessment and Social Control of Technology - Lažnjak, Jasminka (2002)
The thories of social construction of technology offered a new approach to evaluation process: costructive technology assessment as active, positive form of shaping technology. One of the key concepts is the idea that basis for decision making must be broadened. From this perspective this papaer analyzes one aspect of already existing instrument of TA in Croatia, obligatory environment impact studies before every technological intervention or project.
Projekt MZOS
ENG